2021
DOI: 10.3389/fmars.2021.800745
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Regulations of Dynamic Methylation and Transcriptional Responses to Recurring Environmental Stresses During Biological Invasions

Abstract: Deoxyribonucleic acid methylation and gene transcription have been proved as two underlying mechanisms involved in rapid plastic response to environmental stresses. However, it remains elusive on how DNA methylation regulates gene transcription under acute and recurring environmental challenges to form the stress memory, further contributing to invasion success during range expansions. Using a model invasive species Ciona robusta, we investigated the regulatory roles of DNA methylation on gene transcription an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Gene expression is among the most well-known molecular plastic traits, mainly because transcriptional regulations, which link genotypes and phenotypes, can be immediately induced to cope with environmental stresses during many ecological and evolutionary processes ( Fu et al 2021 ; Josephs 2021 ). Many studies have examined the roles of gene expression plasticity in organismal acclimation and adaptation to various environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression is among the most well-known molecular plastic traits, mainly because transcriptional regulations, which link genotypes and phenotypes, can be immediately induced to cope with environmental stresses during many ecological and evolutionary processes ( Fu et al 2021 ; Josephs 2021 ). Many studies have examined the roles of gene expression plasticity in organismal acclimation and adaptation to various environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have shown that epigenetic variation, particularly for the most commonly studied type in animals – DNA methylation – could not only change phenotypic outcomes but also contribute to evolutionary and adaptive potential of wild populations (Adrian‐Kalchhauser et al, 2020; Hu et al, 2019; Hu & Barrett, 2017). Unlike genetic variation, epigenetic variants can be directly influenced by environmental conditions and provide a faster route to respond to environmental change (Fu et al, 2021; Heckwolf et al, 2020; Richards et al, 2017; Verhoeven et al, 2016). Epigenetic changes can also facilitate evolution when stably transmitted across generations or by increasing genetic mutation rate (Schmid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adaptation solely based upon changes in allele frequencies of available genetic variation limits the capacity for wild populations to cope with novel or rapidly changing environments (Hu & Barrett, 2017). Epigenetic changes, such as DNA methylation, can regulate many biological processes such as gene expression to promote phenotypic plasticity without changing underlying genotypes (Fu, Huang, Chen, et al, 2021; Huang et al, 2017). This mechanism can provide a rapid pathway for fine‐tuning phenotypes and “buy time” for genetic adaptation to catch up under rapid environmental changes during the initial stages of colonization (Bogan et al, 2021; Heckwolf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%